Nursing decision-making for health policies during the COVID-19 pandemic in Europe : the ENVISION study - Clari, Marco; Conti, Alessio; Berthelsen, Connie; Bieber, Anja; Brajshori, Naime; Henriques, Adriana; Huber, Claudia; Kane, Ros; Kyranou, Maria; Lethin, Connie ; 0000-0002-2523-8440; Sammut, Roberta; Velonaki, Venetia Sofia; et al. (BMC Nursing, 2026)
Background: The participation of nurse leaders in decision-making has been described as vital for healthcare organisations. However, their involvement in health policy-making is still suboptimal and their contribution is frequently unnoticed. This study aimed to understand the contribution of nurse leaders in decision and policy-making during the COVID-19 pandemic to inform future health crisis management. Methods: A qualitative study using a thematic approach was carried out together with the European Academy of Nursing Science between January 2022 to December 2023. Findings: 74 nurse leaders from 14 different European countries were interviewed. During COVID-19 pandemic, nurse leaders contributed to redesign nursing care delivery, opening COVID wards, designing vaccination units, and readapting nursing students’ curricula. Nurse leaders addressed the uncertainty through shared decision-making, based on real-time knowledge and available evidence. Self-confidence, empathy, and the ability to adapt to a changing situation were considered essential to fulfil their professional duties. Due to the lack of effective ready-made solutions, nurse leaders were concerned about the consequences of their decisions throughout the pandemic, generating feelings of anxiety and uncertainty. Conclusion: The pandemic made the role and competence of nurse leaders more visible, highlighting the importance of their contribution to healthcare systems. Implications for nursing and nursing policy: The results of this study highlight the urgent need for healthcare systems to improve their preparedness for future health crises. Moreover, due to the fundamental contribution that nurse leaders had on the management of the pandemic, from clinical to educational settings, the position of nurse leaders in decision-making processes must be strengthened.
Publisher Copyright: © The Author(s) 2026.
Keywords: Covid-19 pandemic; Decision-making; Health crisis; Health policy; Nurse leadership; Nursing; Preparedness